2015
DOI: 10.18632/oncotarget.6024
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor controls expression of the cancer-associated sTn antigen and cell adhesion through induction of ST6GalNAc1 in prostate cancer

Abstract: Patterns of glycosylation are important in cancer, but the molecular mechanisms that drive changes are often poorly understood. The androgen receptor drives prostate cancer (PCa) development and progression to lethal metastatic castration-resistant disease. Here we used RNA-Seq coupled with bioinformatic analyses of androgen-receptor (AR) binding sites and clinical PCa expression array data to identify ST6GalNAc1 as a direct and rapidly activated target gene of the AR in PCa cells. ST6GalNAc1 encodes a sialytr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 56 publications
5
98
0
Order By: Relevance
“…Induction of ST6GalNAc1 was found to promote a more mesenchymal cell phenotype in prostate cancer cells and to inhibit the formation of stable tumour masses in mouse models. Further analysis of prostate cancer tissue showed that although ST6GalNAc1 is increased in primary tumours, expression is dramatically downregulated in metastatic disease, indicating that ST6GalNAc1 may have a transient role in prostate cancer progression (Munkley et al 2015c). Our analysis of the prostate cancer transcriptome also identified the core 2 branching enzyme GCNT1 as an AR target gene in prostate cancer patients .…”
Section: :3mentioning
confidence: 67%
See 4 more Smart Citations
“…Induction of ST6GalNAc1 was found to promote a more mesenchymal cell phenotype in prostate cancer cells and to inhibit the formation of stable tumour masses in mouse models. Further analysis of prostate cancer tissue showed that although ST6GalNAc1 is increased in primary tumours, expression is dramatically downregulated in metastatic disease, indicating that ST6GalNAc1 may have a transient role in prostate cancer progression (Munkley et al 2015c). Our analysis of the prostate cancer transcriptome also identified the core 2 branching enzyme GCNT1 as an AR target gene in prostate cancer patients .…”
Section: :3mentioning
confidence: 67%
“…Increased expression of sialylated glycans creates negative charges and can inhibit the cell adhesion through electrostatic repulsion (Munkley & Elliott 2016b). We found previously that in prostate cancer cells, the androgen receptor controls the expression of the cancer-associated sTn antigen and cell adhesion through induction of ST6GalNAc1 (Munkley et al 2015c) (Fig. 3).…”
Section: :3mentioning
confidence: 88%
See 3 more Smart Citations